2015
DOI: 10.1007/s00134-015-4075-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fluid responsiveness in 100 critically ill children: the effect of baseline contractility

Abstract: Current paediatric predictors of volume response perform poorly; prediction may be improved if baseline contractility is taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…Reasons for exclusion are detailed in S2 File. Consequently, six studies were ultimately included in our analysis [13, 14, 2023]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for exclusion are detailed in S2 File. Consequently, six studies were ultimately included in our analysis [13, 14, 2023]. …”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [12] reported that SVV was of diagnostic value for fluid responsiveness in adult patients ventilated with tidal volume greater than 8 ml/kg in operating room or intensive care unit. However, in the pediatric population, the predictive value of SVV remains relatively underexplored and the available results are controversial [1315]. We hypothesised that SVV could be of predictive value in predicting fluid responsiveness in children.…”
Section: Introductionmentioning
confidence: 99%
“…[34] In a study for critically ill children, the dP/dt max derived from PRAM has been used as a parameter representing ventricular contractility and shown to track the change according to inotropic use. [35] …”
Section: Discussionmentioning
confidence: 99%
“…Bojan and coauthors also hypothesized that cardiopulmonary bypass would have a significantly greater role than low cardiac output on AKI development. It must be acknowledged that no direct measure of cardiac output was included in their study and its assessment is currently poorly applied in the context of pediatric cardiac surgery [11] and pediatric intensive care [12, 13]: it would be interesting to perform a similar analysis including direct cardiac output estimation.…”
Section: Main Textmentioning
confidence: 99%